Beyond the word, within the sign: Inquiry into pre-school children’s handmade pictures about schooling - Elisabet Malmström (Education Inquiry, 2011)
This article reports reflections on a study addressing the role of a handmade picture in understanding pre-school children’s ideas about their future school context. How is it possible to handle communication by pictures dealt with in the framework of a general theory of signs to signify inquiry? The underlying aim of the study and related report are to deepen educational insights into drawing as communication, co-operation and discovery with meaning. This purpose will contribute to a deeper understanding of the role of picture breakdown and a semiotic modal-specific qualifying conversation within integrative pedagogy. Interviews, picture explication as well as the children’s and teachers’ comments are my empirical resources. The result features the children’s style and orientation to sign-mindedness, the pictures’ composition, and children’s discovery of the object with meaning and at the end a considered “figure of thought” from reconstruction the sign with a semio-cognitive potential